Capability Model of Manage Human Resource And Service Agreement at PT X - Inez Gavrila Wahyudi; Johan Setiawan; Wella Wella (Universitas Multimedia Nusantara, 2017)
This research was made with purpose to measure the capability of human resource and work management in PT. X using COBIT 5.0. In the assessment process, researcher applied 1 domain (align, plan, and organize) with 2 processed, Manage Human Resource APO 07) and Manage Service Agreement (APO 09). Data collection was obtained from the distribution of questionnaires to IT division (there were 127 items of the question and 10 respondents). The result of this research figured out that APO 07 stopped in level 2 with score 82.50 in level 3 and APO 09 ended in level 3 with score 84.10 in level 4. In conclusion, there were still few problems that made human resources in PT X unable to reach level 5. PT.X ought to do audit regularly in deep and holistically. Keywords— Align Plan and Organize, Capabilities Level, COBIT 5.0, Manage Human Resources, Manage Service Agreement REFERENCES [1] Sumarsono, Sonny. 2003. Ekonomi Manajemen Sumber Daya Manusia. Jakarta: LPFE-UI. [2] Gondodiyoto, Sanyoto. 2003. Audit Sistem Informasi (Pendekatan COBIT). Bekasi : Mitra Wacana Media. [3] ISACA. 2013. COBIT 5 A Business Framework for the Governance and Management of Enterprise IT. USA : Enterprise GRC Solution Inc. [4] ISACA 2013. COBIT 5 for Information Security. USA : Enterprise GRC Solution Inc. [5] Arbie, E. 2000. Pengantar Sistem Informasi Manajemen, Edisi ke-7. Jakarta : Bina Alumni Indonesia. [6] Arikunto, Suharsimi. 2006. Metodelogi Penelitian. Yogyakarta : Bina Aksara. [7] Arikunto, Suharsimi. 2010. Prosedur Penelitian Suatu Pendekatan Praktik. Jakarta : Rineka Cipta. [8] Davis, Chris, Mike Schiller, & Kevin Wheeler. 2011. IT Auditing Using Controls to Protect Information Assets, 2nd Edition. English : Mc Graw Hill. [9] Follet, Mary Parker. 1999. Visionary Leadership and Strategic Management. MCB University Press. Women in Management Review Volume 14. Number 7.Gondodiyoto, Sanyoto. 2003. Audit Sistem Informasi (Pendekatan COBIT). Bekasi : Mitra Wacana Media. [10] Hasibuan,M. 2003. Manajemen Sumber Daya Manusia. Jakarta: PT. Bumi Aksara. [11] Hasibuan,M. 2003. Organisasi dan Motivasi. Jakarta: PT. Bumi Aksara. [12] Herzberg, Frederick. 2006. Perilaku Organisasi Edisi 10. Yogyakarta: Andy. [13] Jogiyanto. 2005. Sistem Teknologi Informasi. Yogyakarta : Andi Offset. [14] ISACA. 2012. COBIT 5 Enabling Processes. USA : Enterprise GRC Solution Inc. [15] ISACA. 2003. Audit and Control of Information System. USA : Enterprise GRC Solution Inc. [16] Kusumah, Wijaya dan Dwitagama Dedi. 2011. Mengenal Penelitian Tindakan Kelas. Jakarta : PT Indeks. [17] Littlejohn, Stephen W. 1999. Theories of Human Communication, 6th Ed. Belmont CA : Wadsworth Publishing. [18] Muhyuzir T.D. 2001. Analisa Perancangan Sistem Pengolahan Data, Cetakan kedua. Jakarta : PT Elex Media Komputindo. [19] O’Brien, James A. 2010. Management Information System (11th Edition). New Jersey: Pearson Prentice Hall. [20] O’Brien, James A. 2005. Pengantar Sistem Informasi: Perspektif Bisnis dan Manjerial (12th Edition). Jakarta: Salemba.